Semantic and lexical features of words dissimilarly affected by non-fluent, logopenic, and semantic primary progressive aphasia - Vonk, Jet M. J. (J Int Neuropsychol Soc, 2019)
OBJECTIVE: To determine the effect of three psycholinguistic variables—lexical frequency, age of acquisition, and neighborhood density—on lexical-semantic processing in individuals with non-fluent (nfvPPA), logopenic (lvPPA), and semantic primary progressive aphasia (svPPA). Identifying the scope and independence of these features can provide valuable information about the organization of words in our mind and brain. METHOD: We administered a lexical-decision task—with words carefully selected to permit distinguishing lexical frequency, age of acquisition, and orthographic neighborhood density effects—to 41 individuals with PPA (13 nfvPPA, 14 lvPPA, 14 svPPA) and 25 controls. RESULTS: Of the psycholinguistic variables studied, lexical frequency had the largest influence on lexical-semantic processing, but age of acquisition and neighborhood density also played an independent role. The results reflect a brain-language relationship with different proportional effects of frequency, AoA, and ND in the PPA variants, in a pattern that is consistent with the organization of the mental lexicon. Individuals with nfvPPA and lvPPA experienced a neighborhood density effect consistent with the role of inferior frontal and temporoparietal regions in lexical analysis and word form processing. By contrast, individuals with svPPA experienced an age of acquisition effect consistent with the role of the anterior temporal lobe in semantic processing. CONCLUSIONS: The findings are in line with a hierarchical mental lexicon structure with a conceptual (semantic) and a lexeme (word-form) level, such that a selective deficit at one of these levels of the mental lexicon manifests differently in lexical-semantic processing performance, consistent with the affected language-specific brain region in each PPA variant.